Provenance of basement erratics in Quaternary coastal moraines, southern McMurdo Sound, and implications for the source of Eocene sedimentary rocks - F. M. Talarico; R. H. Levy; PACE, DONATO (2013)
This paper summarizes fieldwork conducted in 2007 and presents results of petrographical analyses of basement rocks that occur along with fossil-rich Eocene sedimentary erratics in moraines along the north-east flank of Mount Discovery in southern McMurdo Sound. The Eocene rocks are significant as they provide a rare glimpse into greenhouse environments at high southern latitudes. Basement erratics recovered from the moraines are petrographically similar to metamorphic and igneous rocks exposed in the Transantarctic Mountains at locations between the Carlyon and Skelton glaciers and/or within the drainage catchments of Mulock and Skelton glaciers. These new clast provenance data imply that the Eocene sedimentary erratics are most likely derived from outcrops that are currently located beneath the Ross Ice Shelf south and/or immediately east of Minna Bluff. The suite of basement and sedimentary erratics were transported to their present location by ice that flowed north-eastwards from the Skelton-Mulock region and was pushed westwards into southern McMurdo Sound by grounded ice flowing north from West Antarctica. Results from this study support prior reconstructions of ice flow during peak glacial intervals during the Miocene–Pleistocene including the Last Glacial Maximum.